2022
DOI: 10.1002/art.42333
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐to‐Lymphocyte Ratio and Platelet‐to‐Lymphocyte Ratio as Biomarkers in Axial Spondyloarthritis: Observational Studies From the Program to Understand the Longterm Outcomes in Spondyloarthritis Registry

Abstract: Objectives This study was conducted to assess the utility of neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) in predicting radiographic sacroiliitis and active disease in axial spondyloarthritis (SpA) and to explore the association between use of a tumor necrosis factor inhibitor (TNFi) and these laboratory values compared with traditional inflammatory markers. Methods Observational data from the Program to Understand the Longterm Outcomes in Spondyloarthritis (PULSAR) registry were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…PLR is an easy-to-obtained inflammatory biomarker calculated as the ratio of the platelet to lymphocyte count. Previous studies had applied PLR in several inflammatory disorder conditions, including solid tumors 17 , arthritis 18 , and acute kidney injury 19 . These studies indicated PLR could be a useful biomarker to indicate the disease activity, treatment reaction, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…PLR is an easy-to-obtained inflammatory biomarker calculated as the ratio of the platelet to lymphocyte count. Previous studies had applied PLR in several inflammatory disorder conditions, including solid tumors 17 , arthritis 18 , and acute kidney injury 19 . These studies indicated PLR could be a useful biomarker to indicate the disease activity, treatment reaction, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Костное воспаление, выявляемое в крестцово-подвздошных сочленениях у пациентов с ранним СпА и у трансгенных крыс, экспрессирующих HLA-B27, характеризуется выраженным нейтрофильным компонентом [186,187]. В крови пациентов с АС наблюдается увеличение уровня нейтрофилов, ассоциирующееся с прогрессированием поражения позвоночника [188]. Активация оси ИЛ-23/ИЛ-17 приводит к рекрутированию и активации нейтрофилов, связанных с синтезом ИЛ-8 [189,190].…”
Section: спондилоартритыunclassified
“…Similarly, it has been reported that a high initial CLR ratio detected in COVID‐19 patients is a predictor of poor prognosis 14 . Rouhin Sen and colleagues have reported a relationship between NLR and PLR in predicting radiographic sacroiliitis and active disease in axial spondyloarthritis (SpA), which could assist in the management of SpA when evaluated in conjunction with clinical findings 15 …”
Section: Introductionmentioning
confidence: 95%
“…14 Rouhin Sen and colleagues have reported a relationship between NLR and PLR in predicting radiographic sacroiliitis and active disease in axial spondyloarthritis (SpA), which could assist in the management of SpA when evaluated in conjunction with clinical findings. 15 However, to our knowledge, these inflammatory markers have not been collectively evaluated in sacroiliitis. Therefore, our aim was to investigate inflammatory markers (PLR, NLR, LMR, CLR) in patients with and without sacroiliitis, and also to evaluate the differences in these markers between active and chronic sacroiliitis patients.…”
Section: Introductionmentioning
confidence: 99%